The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/1744806920958596
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning-based automated phenotyping of inflammatory nocifensive behavior in mice

Abstract: The discovery and development of new and potentially nonaddictive pain therapeutics requires rapid, yet clinically relevant assays of nociception in preclinical models. A reliable and scalable automated scoring system for nocifensive behavior of mice in the formalin assay would dramatically lower the time and labor costs associated with experiments and reduce experimental variability. Here, we present a method that exploits machine learning techniques for video recordings that consists of three components: key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…The discrepancy between these results could be explained by difference in timing of tissue collection, route of administration, and C57BL/6 substrain differences that could affect these results (52). Indeed, we and others recently reported that C57BL/6J and C57BL/6N substrains differ in their responses in acute and tonic pain models (53)(54)(55).…”
Section: Discussionmentioning
confidence: 88%
“…The discrepancy between these results could be explained by difference in timing of tissue collection, route of administration, and C57BL/6 substrain differences that could affect these results (52). Indeed, we and others recently reported that C57BL/6J and C57BL/6N substrains differ in their responses in acute and tonic pain models (53)(54)(55).…”
Section: Discussionmentioning
confidence: 88%
“…org/ impre ss/ Pipel ineIn fo? id= 15; pain pilot study, Wotton et al 2020; https:// www. mouse pheno type.…”
Section: Discussionmentioning
confidence: 99%
“…respiration, inflammation), in some cases only in centre-specific pipelines or pilot studies (e.g. immunophenotyping, https://www.mousephenotype.org/impress/PipelineInfo?id=15 ; pain pilot study, Wotton et al 2020 ; https://www.mousephenotype.org/understand/data-collections/pain/ ). The goal of the IMPC is to ascribe altered physiological function in the presence of a null mutation, hence additional challenges are intentionally minimised to increase the signal of the mutated genotype.…”
Section: Discussionmentioning
confidence: 99%
“…Advances in the Fourth-generation RNA-seq platforms, especially in situ sequencing (ISS) and fluorescent ISS (FISSEQ), have greatly helped to achieve the objectives and aims of RNA-seq techniques [ 69 , 74 ]. ISS technique is highly sensitive and involves the use of padlock probes and rolling circle amplification (RCA) to generate targeted sequencing libraries, which are later sequenced by the application of NGS techniques.…”
Section: Spatial Transcriptomicsmentioning
confidence: 99%